Impact of health education on knowledge and practices about menstruation among adolescent school girls of rural part of district Ambala, Haryana - Arora, A; Mittal, A; Pathania, D; Singh, J; Mehta, C; Bunger, R (Indian Journal of Community Health, 2013)
Background: This study was undertaken to assess the impact of health education on knowledge regarding menstruation, misconceptions related to it as the prevalence of RTI is still very high in India. Aims: To study the existing level of status of hygiene, knowledge and practices regarding menstruation among adolescent school girls and to assess the change in their knowledge level and practices after health education. Materials A community-based pre and post interventional study was conducted among 200 adolescents’ girls of class IX and X of rural part of district Ambala. Multistage random sampling technique was used to draw the representative sample. A pre-tested questionnaire was administered and later health education regarding menstruation and healthy menstrual practices was imparted to the girls. Post-test was done after 3 months to assess the impact of health education. Pre- and post-intervention, data were compared using the paired t test, z test for proportions, chi-squared test for paired proportions. Difference between Proportions of the pre-post data and its 95% confidence interval has been calculated of the findings. SPSS for Windows software version 20 (IBM, Chicago, USA) have been used for data analysis. The level of significance has been considered at p value < 0.05. Results: In the pre-test, menstrual perceptions amongst them were found to be poor and practices incorrect while in the post-test, there was a significant difference in the level of knowledge (P<0.05). There was no significant difference in pre and post-test with regard to restrictions followed during menses (P>0.05) while in the post-test preceding health education, significant improvements were observed in their practices. Conclusion: Overall significant improvement was found in knowledge and practices regarding menstruation among adolescent school girls.